Transfer Pricing Settlement in Indonesia: A Note for Tax Authority, Tax Court, and Taxpayers based on the Tax Court Decisions - Tambunan, Maria R.U.D. (UI Scholars Hub, 2022)
Transfer pricing disputes have been quite high and have been considered as an important issue in taxation system in Indonesia. The high level of these disputes should be a common concern, especially to examine how the dispute process occurred and how to resolve it. This study aims to discuss the tax auditor, taxpayer, and tax court judge behavior’s prior to the transfer pricing issue and how to reduce the dispute. This study uses tax court decisions settled year 2015-2019 as the locus of the study. The research uses qualitative approach and qualitative method. The data was collected from the study documentation, literature review and interview to the key informants. The research shows that the increase of transfer pricing disputes might be caused by the aggressive tax audit behavior. This aggressive tax audit behavior resulted the less reliable audit finding that lead the taxpayer to submit the appeal to the tax court. Unfortunately, for many cases, the tax court decision seemed inconsistent. No certain indicators stated by the judges that a transaction has or has not satisfied the arm’s length principle. Thus, tax court decision could not sufficiently be considered as a reference for future potential case. With this phenomenon, the tax auditor needs to increase the competence and comply with the tax audit guideline. Similarly, the taxpayer also needs to fully disclose their transfer pricing documentation. Finally, the judges should improve their expertise on transfer pricing and follow the international business dynamics.